The effect of Zn-Ni sublayers on the corrosion behaviour and thermal stability of epoxy coatings electrodeposited on steel - Mišković-Stanković Vesna B.; Bajat Jelena B.; Maksimović Miodrag D.; Kačarević-Popović Zorica M. (Journal of the Serbian Chemical Society, 2000)
The electrochemical and transport properties, as well as the thermal stability of epoxy coatings electrodeposited on steel and steel modified by Zn-Ni alloys were investigated during exposure to 3% NaCl. The Zn-Ni alloys were electrodeposited on steel using direct and pulse current. From the time dependence of the pore resistance of the epoxy coating (impedance measurements), the diffusion coefficient of water through the epoxy coating (gravimetric liquid sorption measurements) and the thermal stability of the epoxy coating (thermogravimetric analysis), it was shown that Zn-Ni sublayers significantly improve the corrosion stability of a protective system based on an epoxy coating. The values of the pore resistance were almost unchanged over a long period of immersion time for epoxy coatings on steel modified by Zn-Ni alloys, inidicating the great stability of these protective systems.